STRATEGI PENGEMBANGAN FASILITAS UMUM PASAR WISATA KOTA BUKITTINGGI - Suwita, Suwita; Chair, Ira Meirina; Suyuthie, Hijriyantomi (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
This research aims to determine the development strategy of public facilities that have internal indicators are strengths and weaknesses, and than external indicators are opportunities and threats. This research was descriptive research with qualitative data. Technique of data collected by using interviews, observation and documentation. Determination of informants using Purposive Sampling technique, and Snow-Ball Sampling. Strategy for the development of public facilities Tourism Market are strategic location and the availability of land can be utilized to build unavailable facilities such as waiting areas and children's playgrounds, improving parking systems such as building special parking spaces for the two-wheeled and four-wheeled vehicles, As well as making programs such as